The EFFECTIVENESS OF USING WALKING GALLERY IN IMPROVING SPEAKING ABILITY OF RECOUNT TEXT AT GRADE X KULINER 2 SMKN 9 PADANG - Cindy Permata Sari; Suparmi; Rahma Dania (Cahaya Ilmu Bangsa Institute, 2023)
The purpose of this study was to determine the significant effect of using the Walking Gallery strategy on students' speaking ability in recount text. This research was conducted at SMKN 9 Padang. The researcher took a sample by using a purposive sampling technique with certain considerations and in accordance with the researcher goals, students at grade X kuliner 2 had criteria that matched the research objectives, therefore the researcher chose a sample in class X kuliner 2 with 33 students. They were taught by using the Walking Gallery strategy. The research method was quantitative with a pre-experimental approach. The instrument of the data collection was a speaking test. The group were given a pre-test and post-test and this test was conducted to see whether the used of the Walking Gallery strategy can improve students' speaking ability or not. After the data was collected, then the data was analyzed using the t-test formula. The results of the analysis showed that the t-test (26.3) was higher than the t-table (2.03) with a significant level = 0.05. The result showed that alternative hypothesis (Ha) has been accepted, whereas null hypothesis (H0) has been rejected. This indicates that there was a significant effect of using the Walking Gallery strategy on students' speaking ability in recount text.